The Holocaust : the basics - Bartrop, Paul R. (Paul Robert), 1955- (New York : Taylor and Francis, 2019)
"The Holocaust: The Basics is a concise introduction to the study of this seismic event in mid twentieth-century human history. The book takes an original approach as both a narrative and thematic introduction to the topict, and provides a core foundation for readers embarking upon their own study. Suppported by a chronology, glosary, questions for discussion and boxed case studies that focus the reader's thoughts and develop their appreciation of the subjects considered more broadly, The Holocaust: The Basics is the ideal introduction to this controversial and widely-debated topic for both students and the more general reader"--
1. Introduction: Defining the Holocaust -- 2. Outlines, origins, and consequences -- 3. Perpetrators of the Holocaust -- 4. Jews and other victims -- 5. Rescue from the Third Reich and the Holocaust -- 6. Resistance during the Holocaust -- 7. Ending the Holocaust -- 8 Survivors reflect on the Holocaust -- 9 Conclusion: Holocaust memory and the future.
OCLC-licensed vendor bibliographic record.
Keywords: Holocaust, Jewish (1939-1945) -- History